2018
DOI: 10.1159/000486139
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of a Bioluminescence System for the Assessment of Caries Activity on Occlusal Surfaces

Abstract: Objective: Assessment of caries lesion activity is usually performed using visual-tactile criteria. A new approach is to use a system consisting of a photoprotein, which is specific for free calcium ions, along with an integrated camera that visualizes the elevated calcium ions on the lesion as a light signal (bioluminescence). This study aimed to evaluate the reproducibility and diagnostic accuracy of a newly developed bioluminescence system to assess caries lesion activity on occlusal surfaces in vitro. Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…In the present in vivo study, a bioluminescence device (Calcivis imaging System, Cis) was used to monitor the occlusal surfaces of permanent teeth, and the findings were compared with visual assessments based on ICCMS criteria for lesion activity assessment [17]. The Cis measurements were not significantly different from the values obtained in the visual assessment, confirming the results of previous in vitro studies [7].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In the present in vivo study, a bioluminescence device (Calcivis imaging System, Cis) was used to monitor the occlusal surfaces of permanent teeth, and the findings were compared with visual assessments based on ICCMS criteria for lesion activity assessment [17]. The Cis measurements were not significantly different from the values obtained in the visual assessment, confirming the results of previous in vitro studies [7].…”
Section: Discussionsupporting
confidence: 77%
“…A sample size calculation was performed using the software PASS 11, NCSS, version 11.0.7 (Kaysville, UT, USA), based on data of a preliminary in vitro study assessing the agreement between visual and bioluminescence measurements and diagnostic accuracy of activity assessment [7]. A total of 48 occlusal surfaces were calculated for a power of 0.95 and α = 0.05.…”
Section: Sample Size Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel bioluminescence technology, the CALCIVIS Imaging System, has been developed to aid in the assessment of caries lesion activity. An in vitro study on occlusal sites of extracted teeth, using a pH dye for validation of activity, demonstrated: (a) a sensitivity of 92.5%; (b) a specificity of 90%, and (c) a diagnostic accuracy for activity assessment of caries lesions which was not significantly different from the value obtained using the ICDAS activity assessment method (Jablonski-Momeni et al, 2018), which was the validated activity assessment method used in the current article-vide infra. The technology underlying the CALCIVIS imaging system was developed to help address this unmet need.…”
Section: Introductionmentioning
confidence: 71%
“…Another study showed lower sensitivity and specificity values for the bioluminescence system compared to the fluorescence-based system when active initial lesions were detected on occlusal surfaces [8]. However, the results were based on visual assessment of the teeth as a reference, so that the results cannot be compared to the study by Jablonski-Momeni et al [17] due to the lack of histological findings. Longbottom et al [19] used the bioluminescence technology for assessment of artificially produced demineralization in dental enamel at different pH values such as acidic solutions.…”
Section: Discussionmentioning
confidence: 96%